Epigenetic Profiling of Tumor Suppressor Genes Methylation in Breast Cancer Using the MS-MLPA Method - Zhafira, Alifya; Adhitya Bayu Perdana; Botista Agung Maryanto; Muhaimin Rifa'i (Universitas Brawijaya, 2026)
Breast cancer remains the leading cause of cancer-related mortality among women globally, with a high incidence rate reported in Indonesia. Early detection is essential for improving the prognosis and therapeutic outcomes. DNA methylation of tumour suppressor genes (TSGs) has emerged as a promising biomarker for cancer diagnosis. This study aimed to identify the methylation status of TSGs in breast cancer tissues using the Methylation-Specific Multiplex Ligation-Dependent Probe Amplification (MS-MLPA) method. A total of 44 breast cancer tissue samples and three normal tissues (negative controls) were obtained from the Biobank of Dharmais Cancer Hospital. DNA was extracted and analysed using the ME001-D1 probemix (MRC-Holland) according to the manufacturer’s instructions. Methylation status was evaluated using Coffalyser.Net. of the 44 samples analysed, 20 (45.4%) exhibited promoter methylation in one or more TSGs, whereas 24 samples (54.6%) showed no methylation. Methylation was identified in nine genes: RASSF1, CDKN2A, APC, CDH13, GSTP1, DAPK, CADM1, BRCA1, and TIMP3. RASSF1 showed the highest frequency (75%), followed by CDKN2A (40%) and APC (30%). Genes such as CDH13, GSTP1, and others appeared at lower frequencies. These findings confirm that aberrant DNA methylation of TSGs plays a critical role in breast cancer pathogenesis. Further studies are recommended to validate the diagnostic value of these genes and explore their potential clinical applications in breast cancer management.